THE INFLUENCE OF THE AMOUNT OF MIGRAN WORKERS TO THE GROWTH OF FOREIGN EXCHANGE RESERVE IN INDONESIA - Eva Diana; Andria Zulfa (Journal of Malikussaleh Public Economics, 2019)
This study aims to determine the effect of the number of Migrant Labour abroad to the growth of foreign exchange reserve in Indonesia. This study uses the number of sending workers abroad and foreign exchange reserve in the year 1999-2017. The study utilizes simple regression method. The results of the study indicated that the number of Indonesian Workers had no effect on the foreign exchange reserve from 1999-2017.